2020
DOI: 10.1111/eva.12946
|View full text |Cite
|
Sign up to set email alerts
|

Sources of epigenetic variation and their applications in natural populations

Abstract: Epigenetic processes manage gene expression and products in a real‐time manner, allowing a single genome to display different phenotypes. In this paper, we discussed the relevance of assessing the different sources of epigenetic variation in natural populations. For a given genotype, the epigenetic variation could be environmentally induced or occur randomly. Strategies developed by organisms to face environmental fluctuations such as phenotypic plasticity and diversified bet‐hedging rely, respectively, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 214 publications
(288 reference statements)
0
48
0
Order By: Relevance
“…Seed set is negatively affected by cold conditions, with diploids having significantly lower abortion rates under both temperature conditions, while tetraploids produced only a handful of well-developed seeds under warm conditions. Cold and frost conditions decrease seed set and injure the reproductive tissues of alpine plants, e.g., in Saxifraga bryoides [ 120 ] and Ranunculus hirtellus [ 121 ]. Moreover, Ladinig et al [ 122 ] suggested that the repeated moderate frost treatment, applied also here, mimics temperature conditions occurring in high mountains and provokes frost injury in reproductive shoots, which could also result in full fruit loss.…”
Section: Discussionmentioning
confidence: 99%
“…Seed set is negatively affected by cold conditions, with diploids having significantly lower abortion rates under both temperature conditions, while tetraploids produced only a handful of well-developed seeds under warm conditions. Cold and frost conditions decrease seed set and injure the reproductive tissues of alpine plants, e.g., in Saxifraga bryoides [ 120 ] and Ranunculus hirtellus [ 121 ]. Moreover, Ladinig et al [ 122 ] suggested that the repeated moderate frost treatment, applied also here, mimics temperature conditions occurring in high mountains and provokes frost injury in reproductive shoots, which could also result in full fruit loss.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, pronounced and stable epialleles resulting from spontaneous loss of DNA methylation can generate heritable phenotypic variation and can be seen as a form of diversified bet-hedging strategy. On the other hand, moderate and transient epialleles induced by the environment provide a means to generate rapid and transient phenotypic plasticity [140]. However, this second flavour of epimutations appears to be of little adaptive potential in the face of abrupt environmental changes, except perhaps when environments fluctuate.…”
Section: (C) Evolutionary Significance Of Te-associated Epiallelic Vamentioning
confidence: 99%
“…However, this second flavour of epimutations appears to be of little adaptive potential in the face of abrupt environmental changes, except perhaps when environments fluctuate. Indeed, modelling suggests that by enabling a rapid loss of stress memory, transient epimutations may be advantageous in the latter context [141][142][143], and especially when environmental changes are relatively predictable [140,[144][145][146][147].…”
Section: (C) Evolutionary Significance Of Te-associated Epiallelic Variationmentioning
confidence: 99%
“…To date however, there has been only a limited number of studies in fish because it is difficult to disentangle the different effects due to genetic variation among individuals. In this context, the use of asexual fish vertebrate models, such as the clonal fish Chrosomus eos-neogaeus (Cyprinidea), that reproduces asexually through gynogenesis, has been pioneering as it allowed to have biological replicates without genetic variation (reviewed in Angers et al, 2020). Several studies using this biological model in natural populations have revealed that i) levels of DNA methylation variation were higher than genetic variation (Massicotte et al, 2011); ii) both environmentally induced and stochastic modifications of DNA methylation were sources of epigenetic variation (Massicotte and Angers, 2012;Leung et al, 2016); iii) the relative abundance of environmentally induced and randomly established epigenetic marks was correlated to the predictability of environmental conditions, both in natural sites and common garden experiments (Leung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of epigenetic processes such as DNA methylation in mediating environmentally induced phenotypic variation has been reviewed in Angers et al (2010). To date, only a limited number of studies in fish could independently analyse genetic and epigenetic variations, using asexual fish vertebrate model systems such as the clonal fish Chrosomus eos-neogaeus (Cyprinidea) (Angers et al, 2020) or the naturally self-fertilizing hermaphroditic mangrove killifish Kryptolebias marmoratus (Ellison et al, 2015;Berbel-Filho et al, 2019). However, the aforementioned studies were limited to a single or a few genotypes.…”
Section: Introductionmentioning
confidence: 99%